Br-IndustrialExpert: um framework para análise de dependabilidade de processos industriais - Macedo, Daniel Enos Cavalcanti Rodrigues de (2014)
There is a growing need to develop new tools to help end users in tasks related to the design, monitoring, maintenance and commissioning of critical infrastructures. The complexity of the industrial environment, for example, requires that these tools have flexible features in order to provide valuable data for the designers at the design phases. Furthermore, it is known that industrial processes have stringent requirements for dependability, since failures can cause economic losses, environmental damages and danger to people. The lack of tools that enable the evaluation of faults in critical infrastructures could mitigate these problems. Accordingly, the said work presents developing a framework for analyzing of dependability for critical infrastructures. The proposal allows the modeling of critical infrastructure, mapping its components to a Fault Tree. Then the mathematical model generated is used for dependability analysis of infrastructure, relying on the equipment and its interconnections failures. Finally, typical scenarios of industrial environments are used to validate the proposal